2011
DOI: 10.1103/physrevb.84.035440
|View full text |Cite
|
Sign up to set email alerts
|

Moiré butterflies in twisted bilayer graphene

Abstract: The Hofstadter butterfly spectral patterns of lattice electrons in an external magnetic field yield some of the most beguiling images in physics. Here we explore the magnetoelectronic spectra of systems with moiré spatial patterns, concentrating on the case of twisted bilayer graphene. Because long-period spatial patterns are accurately formed at small twist angles, fractal butterfly spectra and associated magnetotransport and magnetomechanical anomalies emerge at accessible magnetic field strengths.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
210
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(222 citation statements)
references
References 31 publications
10
210
1
1
Order By: Relevance
“…Although twisted bilayers with small rotation angles (typically 10 ) appear as a fascinating field of development for the physics of graphene [22,37,38], uncertainties about the mechanism of interlayer interaction remain [36,39]. Here we show that graphene layers rotated between 1 and 10 present singularities in the LDOS.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Although twisted bilayers with small rotation angles (typically 10 ) appear as a fascinating field of development for the physics of graphene [22,37,38], uncertainties about the mechanism of interlayer interaction remain [36,39]. Here we show that graphene layers rotated between 1 and 10 present singularities in the LDOS.…”
mentioning
confidence: 80%
“…In particular, recent scanning tunneling microscopy and spectroscopy (STM and STS) studies have demonstrated the renormalization of the band velocity [35] and the appearance of van Hove singularities in the local DOS (LDOS) [13] of three twisted layers configurations, one measured at the graphite surface and two on few layers graphene (FLG) grown on Ni. At variance, a careful angle resolved photoemission spectroscopy investigation of FLG on the SiC C face detected neither a van Hove singularity nor any significant change in the Fermi velocity in the range 1 < < 10 , and suggests major problems in our current understanding of twisted graphene layers [36].Although twisted bilayers with small rotation angles (typically 10 ) appear as a fascinating field of development for the physics of graphene [22,37,38], uncertainties about the mechanism of interlayer interaction remain [36,39]. Here we show that graphene layers rotated between 1 and 10 present singularities in the LDOS.…”
mentioning
confidence: 99%
“…We now turn to the magnetotransport properties of STA bilayer graphene. The energy spectrum of a 2D electron system subject to a spatially periodic potential, and a perpendicular magnetic field (B) has a fractal structure known as the Hofstadter butterfly, characterized by two topological integers: ν, representing the Hall conductivity in units of e 2 /h, and s, the index of subband filling (31)(32)(33)(34). Gaps in the energy spectrum are observed when the density per moiré unit cell and the magnetic flux per moiré unit cell (ϕ ≡ BA) satisfy the following Diophantine equation:…”
Section: Resultsmentioning
confidence: 99%
“…Here small differences in the orbitally quantized states in two weakly coherence-split bands produces an amplitude modulation of the Landau level spectrum with a period that greatly exceeds the coherence scale, and should be observable by magnetotransport in the weak field regime. Small rotations angles can introduce long spatial Moire periods for twisted bilayers that can be made commensurate with the magnetic length h/eB on accessible field scales, accessing Hofstadter commensuration physics in a new family of materials [34]. The band flattening theoretically predicted for in the small twist angle regime will surely focus attention on many body effects in the low energy physics.…”
Section: Discussionmentioning
confidence: 99%